2014
DOI: 10.1080/13803395.2014.977233
|View full text |Cite
|
Sign up to set email alerts
|

Clock Drawing Test and the diagnosis of amnestic mild cognitive impairment: Can more detailed scoring systems do the work?

Abstract: A simple 6-point scoring system for the Clock Drawing Test did not differentiate between healthy elderly and patients with amnestic mild cognitive impairment in our sample. Complex scoring systems were slightly more efficient, yet still were characterized by high rates of false-positive results. We found psychometric improvement using combined scores from the Mini-Mental State Examination and the Clock Drawing Test when complex scoring systems were used. The results of this study support the benefit of using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…However, a brazilian study showed a low performance of these tests (0.63 and 0.59, respectively; Ladeira et al, 2009 ). Similarly, other study in high educated sample showed same results (0.70 and 0.61, respectively; Rubínová et al, 2014 ). Thus, the discrepancy in these topic could be explained for the differences in educational level of participants and, potentially, other regional features.…”
Section: Discussionsupporting
confidence: 73%
“…However, a brazilian study showed a low performance of these tests (0.63 and 0.59, respectively; Ladeira et al, 2009 ). Similarly, other study in high educated sample showed same results (0.70 and 0.61, respectively; Rubínová et al, 2014 ). Thus, the discrepancy in these topic could be explained for the differences in educational level of participants and, potentially, other regional features.…”
Section: Discussionsupporting
confidence: 73%
“…The reason for this decision was to avoid clock drawings that would be too small and therefore difficult to evaluate in terms of any visual‐spatial impairment. However, as we noted already in our previous work, we did not expect to find a visual‐spatial impairment so profound that it would lead into the inability to draw a circle in our patients, and thus, we believe that our results would not differ dramatically from those that might have been obtained from drawing a clock on a plain sheet of paper (Rubínová et al, ). Lastly, some studies suggest that education may impact clock drawings (Seigerschmidt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two experienced neuropsychologists familiar with the complex scale‐based scoring method of Cohen additionally rated the clock drawings (Cohen et al, ). An adapted version of Cohen et al 's () scoring system proved to be more specific and sensitive to detect patients with aMCI compared with simple scoring systems in our previous study (Rubínová et al, ). The adapted scale comprises of 13 points evaluating construction and 4 points evaluating the concept of time (total of 17 points).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This remains a topic of international interest, reflected in the numerous studies continuously published about the CDT capacity to detect Mild Cognitive Impairment (MCI) and multiple forms of cognitive impairment and dementia (e.g. Aprahamian, Radanovic, Nunes, Ladeira, & Forlenza, 2014;Cahn-Weiner et al, 2003;Duro, T abuas-Pereira, Freitas, Santiago, Botelho, & Santana, 2018;Lowery et al, 2003;Mazancova, Nikolai, Stepankova, Kopecek, & Bezdicek, 2017;Parsey & Schmitter-Edgecombe, 2011;Ricci et al, 2016;Rubinov a et al, 2014;Tan, Herrmann, Mainland, & Shulman, 2015;Terwindt, Hubers, Giltay, van der Mast, & van Duijn, 2016;Viscogliosi, Chiriac, Andreozzi, & Ettorre, 2016;Yoo & Lee, 2016;Vyhn alek et al, 2017).…”
Section: Introductionmentioning
confidence: 99%